Electron tomography analysis of envelope glycoprotein trimers on HIV and simian immunodeficiency virus virions - Zhu, Ping (National Academy of Sciences, 2003)
We used electron tomography to directly visualize trilobed presumptive envelope (env) glycoprotein structures on the surface of negatively stained HIV type 1 (HIV-1) and simian immunodeficiency virus (SIV) virions. Wild–type HIV-1 and SIV virions had an average of 8–10 trimers per virion, consistent with predictions based on biochemical evidence. Mutant SIVs, biochemically demonstrated to contain high levels of the viral env proteins, averaged 70–79 trimers per virion in tomograms. These correlations strongly indicate that the visualized trimers represent env spikes. The env trimers were without obvious geometric distribution pattern or preferred rotational orientation. Combined with biochemical analysis of gag/env ratios in virions, these trimer counts allow calculation of the number of gag molecules per virion, yielding an average value of ≈1,400. Virion and env dimensions were also determined. Image-averaging analysis of SIV env trimers revealed a distinct chirality and strong concordance with recent molecular models. The results directly demonstrate the presence of env trimers on the surface of AIDS virus virions, albeit at numbers much lower than generally appreciated, and have important implications for understanding virion formation, virus interactions with host cells, and virus neutralization.